(untitled) (Indian Journal of Animal Production and Management, 2024)
Data of 294 Kankraj cows maintained at Livestock Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat and spread over a period of 20 years (1996 to 2015) was collected to study the repeatability parameters of different traits. The repeatability estimates of 305 days milk yield, total milk yield, lactation length, service period, dry period and gestation period was calculated and found that it was 0.49± 0.03, 0.50± 0.03, 0.24± 0.02, 0.22 ± 0.05, 0.48 ± 0.04 and 0.29 ± 0.09, respectively. Higher estimate of repeatability of total milk yield indicates that the permanent environmental fractions of variance was high. Therefore, the first lactation of cows in the herd will able to predict accurately the subsequent lactation yield and thus lifetime production. Further, more efficient selection can be done after completion of first lactation of the dams.